O PAPEL DOS PCN'S: O ENSINO DE HISTÓRIA NO BRASIL - Henrique R. Silva; Jackeline C. A. Oliveira; Alba R. A. Arana (Universidade do Oeste Paulista, 2016)
The teaching of history must develop the student's reflection awakening understanding of world history and the society in which it is inserted. Thus, this study aimed to verify the NCPs and their proposals for the teaching of history, presenting the alternative languages for teaching history present in the PCNs. We analyze and discuss the reality of history teaching in state school in the city of Sandovalina - SP. The research was bibliographical and field with a qualitative approach, the technique used was the interview. We know that the school is a learning construction environment in which teaching and learning procedure should provide the students to develop their thinking, and this procedure is up to the teacher to question how the student will understand what the teacher seized in university.